Crop, livestock, and forestry integration to reconcile soil health, food production, and climate change mitigation in the Brazilian Cerrado: A review - Oliveira, Dener M.S.; Santos, Rafael S.; Chizzotti, Fernanda H.M.; Bretas, Igor L.; Franco, André L.C.; Lima, Renato P.; Freitas, Diego A.F.; Cherubin, Maurício R.; Cerri, Carlos E.P. (Geoderma Regional, 2024)
Integrated crop–livestock (ICL) and crop–livestock–forestry (ICLF) systems have been widely adopted in the Brazilian Cerrado. In this study, we gathered the publications regarding the effects of the ICL and ICLF systems on soil health, plant and animal production, and carbon (C) balance and then synthesized them in comparable terms, aiming to evaluate the sustainability of these systems in a broader and comprehensive approach. On the basis of the evidence from 65 peer-reviewed publications, it was observed that adopting integrated systems can improve soil health in the Brazilian Cerrado. With a few exceptions, positive effects on chemical, physical, and biological indicators of soil health were observed in most of the studies that comprised our data. Accordingly, the results showed that the ICL and ICLF systems can improve plant yield and animal production, but special attention regarding the grazing regime and tree management (e.g., spacing, pruning, and thinning) is required. Moreover, soil C accumulation fully offsets soil N2O emissions, underscoring the feasibility of using the ICL and ICLF systems for decreasing the C footprint of agricultural commodities in this region. The research assembled in this review has undoubtedly advanced our knowledge regarding integrated systems in the Brazilian Cerrado. However, there are still significant knowledge gaps that should be addressed, such as their effects on soil physics and biology. Despite these shortcomings, our literature review demonstrates that the ICL and ICLF systems are essential strategies to intensify agricultural production in the Brazilian Cerrado while ensuring sustainability.